"Burnout" as a result of emotional exhaustion in a profession: sociocultural discourse; SHS Web of Conferences; Vol. 28 : Research Paradigms Transformation in Social Sciences (RPTSS 2015) - Makarenko N. I. Nataljya Ivanovna; Chaplinskaya Ya. I. Yana Igorevna; Kvesko S. B. Svetlana; Shamrova D. P. Daria (2016, 2016)
Title screen